The Effect of Work Engagement, Nurse Resilience, Burnout, Job Satisfaction, and Social Support on Turnover Intention - Fenia Tandy; Grady Ihsan Shaquille; Pauline Henriette Pattyranie Tan (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Turnover intention is critical in hospitals, as high rates disrupt healthcare stability and raise organizational costs. This study aims to examine the direct relationships between work engagement, resilience, burnout, job satisfaction, and social support in explaining nurse turnover intention in a private hospital in Bali. This study used a quantitative, cross-sectional approach, surveying 171 nurses with a structured questionnaire. Data were analyzed using PLS-SEM in SmartPLS to assess the measurement and structural models. The results showed that work engagement had a positive and significant effect on nurse resilience, while nurse resilience had a significant effect on burnout, job satisfaction, and social support. Furthermore, burnout had a significant positive effect on turnover intention, while job satisfaction had a significant negative effect on turnover intention. However, social support and work engagement were not proven to have a significant direct effect on turnover intention. This study concludes that nurse resilience, based on IPMA analysis, plays a significant role in shaping psychological conditions and work attitudes, which impact burnout, job satisfaction, and turnover intention. Therefore, hospitals are advised to improve nurse work engagement and resilience through psychological capacity-building programs, organizational support, and burnout prevention strategies to reduce turnover intention.